In-situ topotactic construction of novel rod-like Bi2S3/Bi5O7I p-n heterojunctions with highly enhanced photocatalytic activities. (1st February 2023) - Ju, Peng; Hao, Lei; Zhang, Yu; Sun, Jianchao; Dou, Kunpeng; Lu, Zhaoxia; Liao, Dankui; Zhai, Xiaofan; Sun, Chengjun
Highlights: Novel 3D rod-like Bi2 S3 /Bi5 O7 I p-n heterostructures with rich OVs were synthesized by an in-situ topotactic ion exchange method. BSI RHs were composed of internal Bi5 O7 I nanobelts and outside networks orderly interwoven by Bi2 S3 nanorods. BSI RHs exhibited a highly enhanced photocatalytic activity. p-n heterostructure and rich OVs led to the efficient separation of photoinduced charge carriers. ⋅O2 − and h + played key roles in the photocatalytic process. Abstract: In this work, a novel Bi2 S3 /Bi5 O7 I p-n heterojunction with three-dimensional rod-like nanostructure was successfully constructed through an in-situ topotactic ion exchange approach. A possible evolution mechanism from Bi5 O7 I nanobelts (NBs) into Bi2 S3 /Bi5 O7 I rod-like heterostructures (BSI RHs) was proposed, depicting the self-assembly process of internal Bi5 O7 I NBs and outside networks interwoven by Bi2 S3 nanorods (NRs), which abided by the Ostwald ripening and epitaxial growth. Owing to the formation of p-n heterojunction and rich oxygen vacancies (OVs), the visible-light absorption ability and separation of photogenerated charge carriers of BSI RHs were highly promoted, leading to a greatly improved photocatalytic ability than that of Bi2 S3 and Bi5 O7 I. BSI-1 exhibited the strongest photocatalytic performance, and almost all rhodamine B (RhB) and Pseudomonas aeruginosa ( P. aeruginosa ) can be thoroughly removed within 90 min. Moreover, a possible photocatalytic mechanism of BSI RHs was proposed based on the tests of active species trapping, electron spin resonance (ESR), photoelectrochemistry (PEC), and photoluminescence (PL) combined with the density functional theory (DFT) simulated computation, validating the dominating roles of · O2 − and h + during the photocatalytic process. This work is expected to motivate further efforts for developing novel heterostructures with highly efficient photocatalytic performances, which presents a promising application prospect in the fields of energy and environment. Graphical abstract: Bi2 S3 /Bi5 O7 I p-n heterojunction with three-dimensional rod-like nanostructure and highly enhanced photocatalytic activity was successfully constructed through an in-situ ion exchange approach. Image, graphical abstract